Content analysis of 3D design elements in gamified virtual reality for viral infection prevention - Ruslam, Muhammad Farid Solihin; Mohamed Ghazali, Nabila Aimi; Che Din, Sharkawi (Universiti Teknologi MARA, Perak, 2025)
This study analyzes the content analysis of gamified virtual reality (VR) 3D design aspects for the prevention of viral infection. The primary goal is to study how some visual and interactive features of VR experiences influence the user and enhance learning outcomes in public health. The core issue under discussion is the lack of a clear understanding of which unique design factors influence the user's interaction and the effectiveness of education within gamified VR, particularly in public health education. Nine 3D components are examined in the examination: environment design, 3D models and assets, user interface and feedback systems, character design, physics and motion simulation, sound design, game mechanics, navigation and locomotion systems, and lighting and atmospheric effects. Findings attest that gamified VR applications are effective in public health education and strongly rely on the strategic incorporation of these 3D components. These elements are crucial in facilitating the change of behaviour during viral outbreaks. The research highlights that well-designed VR elements enhance students' immersion and are core in motivating preventive health practices. The study notes the significance of developers ensuring an egalitarian design strategy in aspects of visual realism, interaction dynamics, and user experience to maximize VR potential as a powerful learning interface in the event of an epidemic or pandemic. Future design should further support user agency, intuitive control, and realistic simulation to maximize the educational and behavioural effectiveness of gamified VR.